DOMINASI AKAD MURABAHAH PADA PRAKTIK PENYALURAN DANA DI BANK SYARIAH - Rita Yuliana; Shelly Febriana Kartasari (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2012)
Dominated murabahah contract phenomena in bank of sharia is really easy to see. Thisthing becomes an evidence that in doing its function of distributing funds, bank of shariajust tend to product which is not sharing benefit base. Further searching related onmotivation of sharia bank in distributing its funds to murabahah product shows thatmurabahah product for bank has level of risk that relatively low. But, for the customers onthat product has no different with credit which is given by conventional bank thatcommanded in giving a fixed margin. That margin calculation in fact still refer to level ofinterest in BI. The phenomena shows that the orientation of sharia bank still limited inprofit and obedience of islamic principle. While in social orientation, to increase thewelfare of society is still not performing well.